1994
DOI: 10.1159/000171456
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Chronic Liver Disease: Pathogenesis, Risk Factors, and Management

Abstract: This article reviews osteoporosis (OP) in adults with chronic liver disease. OP in this setting is characterized in general by low bone turnover. The pathogenesis is unclear but is probably not related to vitamin D abnormalities. Patients at high risk of OP include those with evidence of cirrhosis, hypogonadism, overt calcium malabsorption, steroid therapy and choleostatic liver disease (particularly primary biliary cirrhosis). OP is best managed by adequate calcium intake, regular weight bearing exercise, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 33 publications
(56 reference statements)
0
30
0
1
Order By: Relevance
“…10,13,23,24 After OLT, there is NOTE. Abnormal graft function is defined as at least two liver enzymes Ն1.5ϫ the upper limit of normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,13,23,24 After OLT, there is NOTE. Abnormal graft function is defined as at least two liver enzymes Ն1.5ϫ the upper limit of normal.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of serum PTH and osteocalcin levels in some patients suggests continuing bone remodeling. Copyright 1999 by the American Association for the Study of Liver Diseases B one disease is well recognized in patients with chronic liver disease [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and is usually caused by low bone-turnover osteoporosis. 5,8,9,12 Although orthotopic liver transplantation (OLT) may stabilize or reverse this process, there is further significant postoperative bone loss.…”
mentioning
confidence: 99%
“…Rapid bone loss with a decrease in spinal bone mineral density (BMD) as high as 6.8 ± 5.6% at 6 months and 8.8 ± 7.0% 18 months after renal transplantation [12] is seen, especially in the first year after transplantation. Besides immobilization after transplantation and the use of immunosuppressive regimens, pre-existing osteoporosis and/or osteomalacia [21,22] are risk factors for occurrence of fractures.…”
Section: Introductionmentioning
confidence: 99%
“…17 In our center, it is policy to strongly encourage smoking cessation in transplant candidates in light of the association with alcohol use as well as other negative health consequences. [18][19][20] Meta-analysis demonstrated that at long-term follow-up, participation in a smoking cessation intervention provided during substance abuse treatment was associated with long-term abstinence from alcohol and other drugs. 21 Consistent with these findings, data suggest that 1 year after treatment, smokers who participated in a substance abuse treatment program and initiated smoking cessation on their own were less likely to be diagnosed as alcohol dependent and had more days abstinent from alcohol and other substances than those who started or continued smoking during the follow-up.…”
Section: Discussionmentioning
confidence: 99%